EXPLORING STUDENT PERSPECTIVES ON INTELLECTUAL CAPITAL ROLE WITHIN UNIVERSITY ENVIRONMENTS - Salwa Muda; Che Norhalila Che Mohamed; Musliha Musman; Raziah Bi Mohamed Sadique; Amariah Hanum Hussin (Journal of Academia)
Intellectual capital, encompassing human capital, structural capital, and relational capital, holds a vital role in shaping the educational landscape of universities. As universities seek to provide holistic educational experiences, understanding how students perceive the different dimensions of intellectual capital becomes paramount. By understanding how students view intellectual capital, the university can align its resources and efforts to enhance the learning experience. Despite the growing recognitionof intellectual capital's significance for improvingan organization’s value creation, there is a lack of research on intellectual capital in the universitycontext, particularly regarding students' perceptions. Therefore, this study aims to bridge this gap by investigating students' perceptions of human capital, structural capital, and relational capital, thereby providing insights into the role of intellectual capital in contributing to the university's overall reputation. An online questionnaire surveywas carried out to 130 students from UiTM Cawangan Negeri Sembilan, KampusSeremban. The data were analyzed using IBM SPSS Statistics 25 software. Mean scoreanalyses were conducted to evaluate students' perceptions of intellectual capital. The results show that students have overwhelmingly positive views regarding intellectual capital on average. Their perceptions suggest that they not only recognize but alsoappreciatethe importance of human capital, structural capital, and relational capital within the university environment.It signifies a harmonious alignment between the university's offerings and students' expectations. This alignment can lead to manypositive outcomes, benefitingstudents, faculty, alumni, and other stakeholders.